Ground Water Contamination by Organochlorine Insecticide Residues in the Godavari Plain of Nanded district - Motekar*, S.C. (Recent Research in Science and Technology, 2011)
Residues of several organochlorine insecticides were monitored in the ground water from rural areas in the Godavari river plain of Nanded district for one year (2010-11). Almost all the samples were found to be contaminated with residues of Hexachlorobenzene (HCB) and Dichloro-diphenyl-trichloroethane (DDT). Resides of Aldrin, endosulfan and heptachlor were also detected in large number of samples. The concentrations of aldrin residues greately exceeded the WHO guideline value for drinking water, concentrations of heptachlor and DDT residues also occasionally exceeded the specified limits. Migration of pollutants through ground water recharge with polluted Godawavari River and monsoon rains carrying undegraded residues downwards from the soil surface are thought to be important sources of insecticide contamination of ground water in the region.